Перевірка результатів автоматизованого синтезу перерізу балок мостового крану за критеріями міцності і жорсткості - Коваленко, Валентин Олександрович; Стрелков, Максим Борисович; Стрижак, Всеволод Вікторович; Рубашка, Володимир Петрович; Турчин, Ольга Володимирівна; Гнатенко, Григорій Олександрович (Національний технічний університет "Харківський політехнічний інститут", 2025)
В статті розглянуто порівняльний аналіз мостових кранів. Перший кран має головні балки, що відповідають конструкції серійного крану. В другому випадку – балки мають автоматично синтезований переріз. Для цього крану виконано визначення параметрів перерізу. Проведено моделювання та чисельний розрахунок міцності і жорсткості моста з балками обох конструкцій. Встановлено, що автоматизований синтез перерізу дозволяє створити конструкцію, яка відповідає вимогам безпечної роботи.

The article considers a comparative analysis of bridge cranes. The first crane has main beams that correspond to the design of a serial crane. In the second case, the beams have an automatically synthesized cross-section. A calculation scheme has been drawn up for the bridge crane and the loads have been determined according to European EN standards. For the design of the serial crane, the cross-section dimensions have been determined in accordance with the design documentation. A 3D model has been created based on these data and a numerical calculation of the strength and stiffness of the bridge has been performed. For comparative analysis, the dimensions of the beam cross-section elements have been determined based on statistical regularities and the initial data of the serial crane (load capacity, span, operating mode group), on the basis of which a 3D model of the crane bridge with an automatically synthesized cross-section has been created. For the bridge with an automatically synthesized cross-section, a check of compliance with the strength and stiffness conditions has also been performed. Comparison of the obtained data makes it possible to assess the discrepancy between the safety margins of the serial crane and the synthesized one. It has been established that automated cross-section synthesis allows for the creation of a design that meets the requirements of safe operation.
Verification of the results of automated synthesis of crane beam cross-sections by strength and stiffness criteria
Keywords: мостовий кран; головна балка; переріз; FEM; FEA; overhead bridge crane; main beam; cross section